INFLUENCE OF TEMPERATURE, pH, AND OXIC STATE ON Ca-P DYNAMICS IN FLOODPLAIN WETLAND SEDIMENT: A MICROCOSM STUDY - MANNA, S. K.; SAMANTA, S.; BANDOPADHYAY, C.; SARKAR, K.; SHARMA, A. P.; MAITRA, N. (Journal of the Inland Fisheries Society of India, 2020)
Phosphorus (P) is a limiting nutrient determining the trophic state in freshwater ecosystems. Besides Fe-P interaction, organic matter decomposition is important in sediment P chemistry or release. Although Ca-P often forms the major inorganic P pool in sediment, role of Ca-P in P cycling/ release is not well studied. The present work conducted in laboratory microcosm using freshly collected floodplain wetland sediment showed that lower pH and moderate to high temperature slowly and significantly influence the Ca-P release; redox condition has less defined role. Besides Ca-P dissolution and P release by microbiota, including phosphate solubilizing bacteria, temperature also dictates microbial P requirement and uptake, ultimately determining the available P level in sediment. In winter chemical interactions might majorly regulate the sedimentary P cycle, however, microbial activities play an important role in P mobilization during summer. Key words: Sediment, Ca-P, temperature, pH, redox state, floodplain wetland